"Evaluation of Risk Factors Causing Musculoskeletal Disorders Using QEC Method in a Furniture Producing Unite" - M Mirmohamadi; J Nasl Seraji; J Shahtaheri; M Lahmi; M Ghasemkhani (Tehran University of Medical Sciences, 2004)
The musculoskeletal disorders cover a large percent of occupational diseases; therefore, in order to protect workers from such disorders, there is a need to evaluate workers positions at work in different industries. In a major furniture manufacture located in Tehran, 500 workers were examined. These workers were divided into fourteen working groups, including production lines of water-heater, air condition, electromotor production line, dunnage making hall, plastic hall, smithery, restaurant, store, engineers and supervisors, facilities, transportation, assembly of absorptive refrigerator and drivers. The results from Nordic Questionnaire and performing the evaluation method showed that, there was a significant relevance between outbreak of back pain and workgroups (P=0.005) and between the outbreak of pain in neck and workgroup as well. A significant relevance of P=0.005 indicating that, the working in the above mentioned work-place causes pain in both back and neck. Between other parts of the body and workgroup no significant relevance observed. Among workgroups, there was a significant relevance between the water-heater production line (P<0.005) and pain in the back, and there was also a significant relevance among the work in air-conditioning production line and the plastic injection (P=0.002), causing pain in the neck. The results from Quick Exposure Check (QEC) in one hundred working posture have shown that 10% of them fall into first and second level and 90% of them were categorized in third and forth levels.